LITHUANIAN DIASPORA’S PUBLISHING ACTIVITIES IN THE UNITED STATES IN THE END OF THE 19TH–MID 20TH CENTURIES: PROBLEM OF THE ADDRESSEE - Misiūnas, Remigijus (Knygotyra, 2016)
The article deals with certain aspects of publishing by the first Lithuanian emigration wave into the United States (second half of the 19th – 1914) in the end of the 19th – mid 20th centuries, placing the strongest emphasis on the analysis of the problems related to publications’addressees. The analysis has been based on the periodical publications of the Lithuanian emigrees during the period in question and the research dedicated to the history of the first emigration wave. Even though the first emigration wave to the United Sates was largely based on economic reasons, a small part (compared to the total number of emigrees) of Lithuanians left their native country due to political reasons and later had quite a significant influence on the formation of the Lithuanian community in the territory of the United States, in particular on the development of social and political processes within the Lithuanian community. These emigrees displayed not only concentration into their internal needs but also represented the manifestations of national determination and reflected political processes and ideological fight, characteristic of Europe and Northern America of those times, as well as integration into these processes. Naturally, all this influenced the publishing processes of the emigration wave in question. Within the publishing of these emigrees, two main trends with a number of smaller branches can be identified. One of the major trends was an ambition to reflect and influence the iternal life of the emigration (including religious, social, political and other processes) as well as meet the publishing needs within the community. The other trend was aimed at supporting national liberation movement in Lithuania and represent Lithuanians as an independent nation both in the USA and global level. Periodical publications were targeted not merely at reflecting the life of the colony, where they were published, and meeting publishing needs, but at least the reality of one or several states as well as Lithuanian highlights. Besides, the survival of such publications depended on the distribution range. The publications which crossed the boundaries of one state and were distributed in a greater number of colonies, including the Lithuanian colonies outside the USA and Lithuanian territory, had a greater chance at survival. The number of published copies is also proof of a wider distribution, going far beyond the boundaries of the Lithuanian ghetto. Within the publishing activities, an overlapping of social and political ambitions with commercial aspirations can be identified. Publishing was oriented toward the achievements of those days, both in terms of the content of periodicals, informatikon gathering and presentation, and printing culture. For a long time, the quality of Lithuanian press in the USA by far surpassed the quality of printing in Lithuania (both during its incorporation in the Russian empire and the first years of independence). It could be stated that during Lithuania’s occupation (by Tsarist Russia and Kaizer Germany), the publishers of the Lithuanian diaspora regarded their publications not only as satisfying the needs of the emigration community in the USA, but also as targeting the addressees of Lithuanian colonies in other countries and the Lithuanians living in their native country. After Lithuania regained independence, the reverse process can be observed – namely, that of Lithuanian publishers regarding the emigration community as a market for their publications, whereas politicians and public figures sought to use the diaspora as a place to spread their ideas. Furthermore, representatives of opposition layers were more interested in the support for their ambitions and an opportunity for print their publications, to be distributed later in Lithuania. Apart from the above mentioned publications, some publication plans were made to target the addressees of other nationals. However, they were mostuly political in nature, related to a certain political situation in Lithuania, rather than commercial.